Development Of A Practicum Guide For Reproduction Material In Plants Integrated With Modified Free Inquiry For Class XI SMA/MA - Mimin Mardhiah Zural; Diansi Utami; Abizar Abizar; Nurhadi Nurhadi (Universitas Lambung Mangkurat, 2024)
This study aims to create a practicum guide for reproduction in plants, which is a sub-chapter of regulatory process in plants. The guide is integrated with modified free inquiry to assist and facilitate teachers and students, as well as to establish a more consistent approach to conducting practicum activities in order to achieve learning objectives. This research was R&D and employed the Plomp Model, which comprises three stages, namely introduction, development, and evaluation. The feasibility testing subjects consisted of three students using individual techniques and six students in small groups. The practicality test is conducted by teachers and students from the XI class of SMAN 1 Koto XI Tarusan, Pesisir Selatan Regency. Observation and questionnaires were implemented as data collection techniques. Descriptive analysis is employed to analyse data. The results of this study demonstrated that the practicum guide developed was highly valid (90.90%), highly feasible (85% and 85.83%), and highly practical (96.94% and 89.51%). Consequently, the development of a practicum guide for plant reproduction that is integrated with modified free inquiry can be implemented in the practicum process, as it has satisfied the criteria of validity, feasibility, and practicality in use.